The Effectiveness of Community Engagement Program Towards Urban Poor Community Development: A Study Of MSU MyNeighbours Program - Shufri Johari; Zakmalisa Erna Md Zaki; Noraihan Mohamad; Ain’Shamimi Arifin (Universitas Internasional Batam, 2024)
MyNeighbours initiative has gained significance in recent years, collaborating with Management and Science University (MSU) to support the urban poor. HeARTS, aiming to realize Sustainable Development Goal (SDG) 11: Sustainable Cities and Communities, employs its community project, MyNeighbours, to promote community and collaboration. MyNeighbours, themed